Polaków stosunek do edukacji — w kręgu językowo‍‑kulturowych stereotypów - Wacławek, Maria; Wtorkowska, Maria (Z Teorii i Praktyki Dydaktycznej Języka Polskiego, 2019)
The aim of the article is a reconstruction of a linguistic and cultural fragment of the stereotypical views of Poles — their attitude to education and schooling. The analysis uses research tools developed as part of Polish ethno-linguistic research. The corpus of the work is language data collected in a questionnaire survey in which 140 respondents took part (70 from Poland and 70 from Slovenia). The analysis of statements reflecting a different, because Polish or Slovenian, perspective reveals some discrepancies. Three basic subcategories of Poles’ attitudes towards education and schooling were singled out and described in detail: 1) positive, 2) negative, 3) other. A vast majority of the excerpts contribute to the model of positive perception of Polish education and schooling.